2015
DOI: 10.1186/s12888-015-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations of military divorce with mental, behavioral, and physical health outcomes

Abstract: BackgroundDivorce has been linked with poor physical and mental health outcomes among civilians. Given the unique stressors experienced by U.S. service members, including lengthy and/or multiple deployments, this study aimed to examine the associations of recent divorce on health and military outcomes among a cohort of U.S. service members.MethodsMillennium Cohort participants from the first enrollment panel, married at baseline (2001–2003), and married or divorced at follow-up (2004–2006), (N = 29,314). Those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Moreover, spouses may require their own separate training for serving as a caregiver in an effort to reduce caregiver burden, which has been shown to compromise caregiver health in caregivers of persons with TBI. 53 Given the growing research on divorce and marital strain related to military service in general, 54,55 a family systems-based approach 56 following a TBI among military service members and Veterans should be emphasized in routine rehabilitation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, spouses may require their own separate training for serving as a caregiver in an effort to reduce caregiver burden, which has been shown to compromise caregiver health in caregivers of persons with TBI. 53 Given the growing research on divorce and marital strain related to military service in general, 54,55 a family systems-based approach 56 following a TBI among military service members and Veterans should be emphasized in routine rehabilitation efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Loss has a profound negative impact on mental health in humans, who are sensitive to many different types of losses. Psychosocial loss, such as spousal loss, is strongly associated with the development of depression (Sikorski et al 2014, Wang et al 2015b). Personal physical loss, such as injury, increases symptoms of stress and depression (Wiseman et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Marital stability, which refers to affective and cognitive states along the related actions that are precedent to terminating a relationship ( Booth et al, 1983 ; Amato et al, 2007 ), is a key indicator of well-being ( Karney and Bradbury, 1995 ). A number of studies have shown that separated and divorced couples experience greater risk for mental and physical health problems ( Amato, 2010 ; Wang et al, 2015 ), as well as can have strong negative consequences for their children, such as impacting their children’s mental health, academic and social performance ( Schramm, 2006 ; Amato, 2007 ; Lansford, 2009 ). Since marriage instability is detrimental to the family unit and society ( Orathinkal and Vansteenwegen, 2006 ), the importance of identifying the factors that promote marital stability is overwhelmingly obvious.…”
Section: Introductionmentioning
confidence: 99%